Disclosure of Parental HIV Status to Children: Experiences of Adults Receiving Antiretroviral Treatment at an Urban Clinic in Kampala, Uganda - Charles Peter Osingada; Monica Okuga; Rose Chalo Nabirye; Nelson Kaulukusi Sewankambo; Damalie Nakanjako (AIDS Research and Treatment)
Limited data are available on the experiences of parental HIV disclosure to children in Uganda. We conducted a qualitative study comprising sixteen in-depth interviews and four focus group discussions with parents receiving highly active antiretroviral therapy. Analysis was done using Atlas.ti qualitative research software. Back-and-forth triangulation was done between transcripts of the in-depth interviews and focus group discussions, and themes and subthemes were developed. Barriers to parents’ disclosure included perceptions that children are too young to understand what HIV infection means and fears of secondary disclosure by the children. Immediate outcomes of disclosure included children getting scared and crying, although such instances often gave way to more enduring positive experiences for the parents, such as support in adherence to medical care, help in household chores, and a decrease in financial demands from the children. Country-specific interventions are needed to improve the process of parental HIV disclosure to children and this should encompass preparation on how to deal with the immediate psychological challenges associated with the parent’s disclosure.